2011
DOI: 10.1097/igc.0b013e31822491d0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cervical Cancer Proteins Associated With Treatment With Paclitaxel and Cisplatin in Patients

Abstract: Differentially expressed proteins between cervical cancer tissues pre- and post-NAC with TP were identified by comparative proteomic approach. The NAC therapy with TP down-regulated proteins involved in energy production (glycolytic enzymes) and chaperones but up-regulated proteins involved in apoptosis. These findings shed new light on biomarkers associated with effect of chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
1
9
0
1
Order By: Relevance
“…Apparently, there is a very poor match between proteins responding to ruthenium compounds and those which respond to cisplatin treatment that were identified in previous proteomic studies [27][28][29][30][31]. This observation suggests that the cellular effects and the mode of action of these anticancer ruthenium drugs are profoundly different from those of clinically established, DNA damaging, platinum compounds in line with other literature reports.…”
Section: Proteomic Profiles Of Treated and Control Cellssupporting
confidence: 76%
“…Apparently, there is a very poor match between proteins responding to ruthenium compounds and those which respond to cisplatin treatment that were identified in previous proteomic studies [27][28][29][30][31]. This observation suggests that the cellular effects and the mode of action of these anticancer ruthenium drugs are profoundly different from those of clinically established, DNA damaging, platinum compounds in line with other literature reports.…”
Section: Proteomic Profiles Of Treated and Control Cellssupporting
confidence: 76%
“…eEF1Bγ was downregulated in HepG2 cells treated with Nomura's jellyfish venom used as an anticancer drug (Choudhary et al, 2018). Also, the protein was essentially decreased in cervical cancer specimens taken from patients after treatment with paclitaxel and cisplatin (Liu et al, 2011). eEF1Bγ may be an urine marker of bladder cancer (Chen et al, 2009).…”
Section: Eef1b Proteins In Cancermentioning
confidence: 97%
“…Usually, these neoplasia is negative for estrogen and progesterone receptors, and no association among Hsp27 and these receptors were observed (Stice et al, 2012). In oral cancers, this protein have been overexpressed in more differentiated tumors (Liu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Such data are in fully in line with others (Tozawa- . In the cervix Hsp27 is a marker of cell differentiation, and is highly expressed during the process of squamous metaplasia (Liu et al, 2011). Romanucci et al (2005) suggested that Hsp27 should be regarded as a differentiation marker for keratinocytes, both in normal and in neoplasic canine skin.…”
Section: Discussionmentioning
confidence: 99%